2017
DOI: 10.3389/fcimb.2017.00233
|View full text |Cite
|
Sign up to set email alerts
|

Increased Zinc Availability Enhances Initial Aggregation and Biofilm Formation of Streptococcus pneumoniae

Abstract: Bacteria growing within biofilms are protected from antibiotics and the immune system. Within these structures, horizontal transfer of genes encoding virulence factors, and promoting antibiotic resistance occurs, making biofilms an extremely important aspect of pneumococcal colonization and persistence. Identifying environmental cues that contribute to the formation of biofilms is critical to understanding pneumococcal colonization and infection. Iron has been shown to be essential for the formation of pneumoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 52 publications
(76 reference statements)
1
25
0
Order By: Relevance
“…Those results were confirmed by data collected from the AFM study which pointed out that addition of Zn 2+ greatly changed the adhesive properties of microbial surface and caused formation of bacterial agglomerates. Brown et al [35] also investigated the influence of the zinc on the biofilms formation and their results shown that with the Zn 2+ concentrations increase, the aggregation of bacteria rise too. The described effect was found to be zinc-specific, because another types of ions (copper and manganese) did not affect biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…Those results were confirmed by data collected from the AFM study which pointed out that addition of Zn 2+ greatly changed the adhesive properties of microbial surface and caused formation of bacterial agglomerates. Brown et al [35] also investigated the influence of the zinc on the biofilms formation and their results shown that with the Zn 2+ concentrations increase, the aggregation of bacteria rise too. The described effect was found to be zinc-specific, because another types of ions (copper and manganese) did not affect biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…The pneumococcal growth was detected by measuring optical density at 600 nm (OD 600 ) at different time points. S. pneumoniae planktonic growth was also evaluated by detecting metabolically active bacteria by resazurin staining after 48 h. Bacteria were grown in metal ion-free BHI medium based on a previous report (BHI medium treated with chelex-100) (Brown et al, 2017). In vitro biofilm formation ability of the bacteria, in the presence of ASD, was evaluated using a static microtiter plate assay (Christensen et al, 1982;Yadav et al, 2018).…”
Section: Planktonic Growth and In Vitro Biofilm Growthmentioning
confidence: 99%
“…A more complex approach is needed to ascertain effective blockade of the biofilm formation known to participate in nasopharyngeal colonization and otitis media. Many of the steps in biofilm formation cross over into bacterial aggregation (discussed above) [31,32]. It is clear that the physiology of biofilms and virulence extends to changes in bacterial behavior such as competence and fratricide [33][34][35][36].…”
Section: Multi-modal Protection: Protein Functions Enter the Vaccine mentioning
confidence: 99%